Antibacterial potential from periodontal dressing raw propolis Trigona itama bee based against Porphyromonas gingivalis: experimental research - Suryono Suryono; Resi Manua Yassa; Leo Trido Saputro; Adiguna Putra Walianto; Nur Rahman Ahmad Seno Aji (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2023)
ABSTRACTIntroduction: One of the procedures used in dentistry to address periodontal disease is periodontal surgery, which can lead to open wounds. Periodontal dressing is a dental material that can help with this issue by accelerate the healing of wounds. The aim of the in vitro study was to investigate the potential inhibition of periodontal dressing with the basic formulated from raw propolis Trigona itama bees against Porphyromonas gingivalis bacteria at various rates. Methods: This in vitro study was true experimental study with Porphyromonas gingivalis cultured in agar plate as sample which sample size was calculated using Federer formula. Periodontal dressing with raw propolis formulations were divided into eight groups of 85, 80, 75, 70, 65, 62.5, 60 and 57%, which were then compared with the 100% raw propolis, RESO-PAC™ group, COE-PAK™, and Baer formulations. Antibacterial testing was tested using zone of inhibition test and was calculated by adding up the zone of inhibition of Porphyromonas gingivalis. The data results were then analyzed using one-way ANOVA (p<0.05). Results: The Shapiro-Wilk test results for the normality test show a significance level of 0.05. It means that the data is commonly distributed. the homogeneity test using Levene's statistics has a significance level of p>0.05. This means the data homogenous distributed. The results of statistical analysis using one-way ANOVA showed a p-value=0.001 (p<0.05), which means that there was a significant difference between the treatment groups. The results showed that pure raw propolis had the highest antibacterial with an inhibition zone diameter of 3.4667 mm after RESO-PAC™, followed by periodontal dressing with raw propolis 85% with an inhibition zone of 2.9167 mm, and periodontal dressing with raw propolis 80% with an inhibition zone of 2.5167 mm. However, at concentrations of 75 to 57%, no bacterial inhibition zone was found. Conclusion: Periodontal dressing with raw propolis formulation 85% had the highest antibacterial activity of Porphyromonas gingivalis after 100% raw propolis and RESO-PAC™.Keywords: Trigona itama, antibacterial assay, periodontal dressing, raw propolisPotensi antibakteri periodontal dressing propolis mentah lebah Trigona itama terhadap Porphyromonas gingivalis: Penelitian eksperimental ABSTRAKPendahuluan: Salah satu prosedur yang dapat digunakan untuk merawat penyakit periodontal adalah bedah periodontal yang akan mengakibatkan luka terbuka pada daerah operasi. Periodontal dressing adalah suatu material kedokteran gigi yang dapat membantu dalam proses penyembuhan luka pasca bedah periodontal. Tujuan dari penelitian in vitro ini adalah mengetahui potensi inhibisi periodontal dressing dari formulasi propolis mental lebah Trigona Itama pada Porphyromonas gingivalis dalam beberapa konsentrasi. Metode: Studi ini merupakan penelitian eksperimental murni dengan sampel penelitian bakteri Porpohyromonas gingivalis yang dikultur pada plat agar dengan perhitungan sampel dilakukan menggunakan rumus Federer. Studi ini membagi periodontal dressing propolis mentah menjadi 8 kelompok: 85, 80, 75, 70, 65, 62,5, 60, dan 57% yang dibandingkan dengan propolis mentah 100%, RESO-PAC™, COE-PAK™, dan Baer Formulation. Pengukuran antibakteri dilakukan menggunakan uji zona inhibisi Porphyromonas gingivalis yang dianalisa menggunakan one-way ANOVA (p<0.05). Hasil: Hasil uji normalitas dengan menggunakan uji Shapiro-Wilk menunjukkan nilai signifikansi p>0,05. Hal ini berarti data berdistribusi normal, Hasil uji homogenitas dengan levene’s statistic menunjukkan nilai signifikansi p>0,05, hal ini menunjukan bahwa data homogen. Hasil analisis statistik dengan menggunakan one way ANOVA menunjukkan p-value=0,001 (p<0,05) yang berarti terdapat perbedaan yang bermakna antar kelompok perlakuan. Hasil penelitian menunjukkan propolis mentah memiliki potensi antibakteri paling tinggi dengan diameter zona inhibisi 3.4667 mm setelah RESO-PAC™k, diikuti propolis mentah 85% dengan diameter 2.9167 mm dan propolis mentah 80% dengan diameter 2.5167 mm. Tidak ditemukan zona inhibisi bakteri pada konsentrasi 57% hingga 75%. Simpulan: Periodontal dressing menggunakan konsentrasi 85% memiliki aktivitas antibakteri tertinggi pada Porphyromonas gingivalis setelah propolis mentah 100% dan RESO-PAC™.Kata Kunci: Trigona itama, pengukuran antibakteri, periodontal dressing, propolis mentah